Penerapan Sistem Penunjang Keputusan Dengan Metode Simple Multi Attribute Rating Technique (SMART) Guna Menentukan Promosi Jabatan Karyawan Pada PT. Multi Teknik Engineering - Surya Permana, Galuh; Haryono, Wasis (CV. Shofanah Media Berkah, 2025)
Employee promotion at PT. Multi Teknik Engineering faces challenges in objective assessment. This study develops a decision support system based on the Simple Multi-Attribute Rating Technique (SMART) method to determine employee promotions more efficiently. The web-based system manages employee data and ranking calculations based on predetermined criteria weights. Testing results show that the system improves efficiency, reduces errors, and enhances transparency in promotion decision-making.